Severe Damage Law on the Ground Surface Induced by High-Strength Mining: A Case Study From the Shendong Coal Field in China - Yan, Weitao; Guo, Junting; Chen, Junjie; Tan, Yi; Yan, Shaoge; Yan, Yueguan (Frontiers in Earth Science, 2022)
High-strength mining has the characteristics of shallow buried depth, large mining height and fast mining speed. Under the condition of high-strength mining, the overburden moves violently and the surface damage is serious. It has caused serious ecological security problems in the mining area In order to solve this problem, it is necessary to adopt the technology of restoration while mining. The key to the effective implementation of this technology is to clarify the real-time distribution law and generation mechanism of surface damage. In this paper, the field investigation and theoretical analysis method are used for related research. The results show that the surface strenuous move duration is long, the strenuous move area is large, and the surface discontinuous deformation is fully developed, with the characteristics of stepped crack lags behind the location of working face, the stepped crack spacing and periodic weighting interval are equivalent. Through discussion and analysis, it is found that the cause of serious damage is the strata movement mode of high-strength mining is “two zones” mode. Under the “two zones” mode, the roof is easy to slip instability, the bedrock is completely broken along the direction of bedrock breaking angle, and the weak anti-disturbance ability of the loose layer lead to the surface are severely damaged. The research results can provide reference for the formulation of follow-up ecological real-time restoration measures in similar mines.